The Philosopher’s Diet in Porphyry’s De Abstinentia: Characterizing a Historical Legacy of Minimalism in Food Consumption [Dieta filozofa w dziele Porfiriusza „De Abstinentia”. Charakterystyka historycznego dziedzictwa minimalizmu w konsumpcji pokarmów] - Gamlath, Isha (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
Historical legacy, as an important constituent for the evaluation of the extent to which the past influences the present, sheds much light on some of the broader issues of the relation between the past and the present. One of the components of historical legacy is human food consumption habits. The domain of food consumption habits, in traditional Greek and Roman culture, contains a fairly noticeable diversity as it fluctuates between what seems to be two wide poles of dietary practices such as a simple diet, with the focus on minimalism and health and a luxury diet, with the focus on excess and extravagance. These poles, upon close analysis, have determined the dietary customs of antiquity while also formed a gastronomic identity. The impact of this historical legacy seems to have not only flavored Porphyry’s discussion of the nature of the philosopher’s diet in On Abstinence from Killing Animals but has also served in characterizing an advanced stage of minimalism in Greek and Roman food consumption habits.